Synthesis of ZnO nanoparticles using leaf extract of Tectona grandis (L.) and their anti-bacterial, anti-arthritic, anti-oxidant and in vitro cytotoxicity activities. (21st August 2017) - Senthilkumar, N.; Nandhakumar, E.; Priya, P.; Soni, D.; Vimalan, M.; Vetha Potheher, I.
Abstract : The novelty of this present work is the investigation of the anti-bacterial, anti-arthritic, anti-oxidant and in vitro cytotoxicity activities of green synthesized Zinc Oxide Nanoparticles (ZnO NPs) using leaf aqueous extract of Tectona grandis (L.). Abstract : The novelty of this present work is the investigation of the anti-bacterial, anti-arthritic, anti-oxidant and in vitro cytotoxicity activities of green synthesized Zinc Oxide Nanoparticles (ZnO NPs) using leaf aqueous extract of Tectona grandis (L.). Zinc nitrate acts as the precursor and the leaf extract acts as the reducing agent. The synthesized ZnO NPs are characterized by powder X-ray diffraction (PXRD) analysis and the crystalline size is calculated by the Scherrer formula. FTIR analysis confirms the presence of various functional groups in the leaf extract as well as in the NPs. The UV absorption peak is observed at 360 nm and the calculated energy band gap is found to be 3.4 eV. Dynamic Light Scattering (DLS) analysis shows the stability and particle size of the synthesized ZnO NPs. The crystalline size, shape and surface morphology of the ZnO NPs are determined by using Field Emission Scanning Electron Microscopy (FE-SEM). Green synthesized ZnO NPs exhibited interesting antibacterial activity against Gram-positive and Gram-negative bacteria and exerted excellent DPPH (di(phenyl)-(2, 4, 6-trinitrophenyl)iminoazanium) free radical scavenging activity. They also showed maximum inhibition of protein denaturation (90.46 ± 0.02) and proteinase inhibitory activity (87.68 ± 0.03) at a dose of 200 μg ml −1 respectively. The anticancer activity of ZnO NPs was also tested against normal and cancer osteoblast MC3t3-E1 cell lines and found a reduction in the size of cancer cells.